An evolutionary approach for solving the job shop scheduling problem in a service industry - Milad Yousefi; Moslem Yousefi; Danial Hooshyar; Jefferson Ataide de Souza Oliveira (International Journal of Advances in Intelligent Informatics, 2015)
In this paper, an evolutionary-based approach based on the discrete particle swarm optimization (DPSO) algorithm is developed for finding the optimum schedule of a registration problem in a university. Minimizing the makespan, which is the total length of the schedule, in a real-world case study is considered as the target function. Since the selected case study has the characteristics of job shop scheduling problem (JSSP), it is categorized as a NP-hard problem which makes it difficult to be solved by conventional mathematical approaches in relatively short computation time.